PENGEMBANGAN KEWIRAUSAHAAN DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS COKROAMINOTO PALOPO - Ma'rufi Ma'rufi; Muhammad Ilyas; Aswar Anas; Reski Yusrini Islamiyah (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
Development of Entrepreneurship in Faculty of Teacher Training and Education Cokroaminoto PolopoAbstract. Entrepreneurship among students is important to be developed and fostered from the start by providing entrepreneurial provisions to students while struggling so that students can develop entrepreneurship so that they can become strong entrepreneurs and successfully compete in the world. Various ways to motivate students to be interested in entrepreneurship have been done, but not yet optimal because of coaching that has not been integrated and sustainable. This fact underlies the importance of science and technology-based entrepreneurship development programs at the Faculty of Teacher Training and Education, University of Cokroaminoto Palopo. Faculty of Teacher Training and Education Entrepreneur-ship Development Program FKIP abbreviated method is a multi-year entrepreneurship program at University of Cokfroaminoo Palopo since 2018. The method used is the development of entrepreneurship based on training, mentoring, internships, and business consulting. The implementation team conducted PPK socialization to students before selecting tenants. Coaching activities that have been carried out are entrepreneurship training, assistance in preparing business plans, product packaging, marketing management, technology-based financial management, internships, and business consulting. The results of the implementation of the PPK FKIP Universitas Cokroaminoto Palopo have been carried out in accordance with the program and targets to be achieved. PPK FKIP is an entrepreneurial program with the dimension of innovation in business creation that synergizes the business world with the world of education using the Warung Pendidikan technique, abbreviated as Warpen. Over the past two years ten new entrepreneurs have been produced. The first year tenants are Accessories Warpen, Decoration Warpen, Tutoring Warpen, Data Analysis Warpen, and Design Warpen. Business fields in the second year, namely the Warpen Makeup, Miniature Warpen, Culinary Warpen, Gymnastics Warpen, and Translater Warpen.Keywords: Development, entreprenurship, warpen, college students, alumny.Abstrak. Kewirausahaan di kalangan mahasiswa penting untuk dikembangkan dan dibina sejak awal dengan memberi bekal kewirausahaan kepada mahasiswa sekaligus sebagai motivasi agar mahasiswa dapat mengembangkan kewirausahaan sehingga dapat menjadi pengusaha yang tangguh dan sukses menghadapi persaingan global. Berbagai cara untuk memotivasi mahasiswa agar tertarik untuk berwirausaha telah dilakukan, namun hasilnya belum optimal karena pembinaan yang belum terintegrasi dan berkelanjutan. Fakta tersebut melatarbelakangi pentingnya program pengembangan kewirausahaan berbasis ilmu pengetahuan dan teknologi di Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Palopo. Program Pengembangan Kewirausahaan Fakultas Keguruan dan Ilmu Pendidikan Metode disingkat PPK FKIP merupakan program kewirausahaan multi tahun di Universitas Cokfroaminoo Palopo sejak tahun 2018. Metode yang digunakan pengembangan kewirausahaan yaitu pelatihan, pendampingan, magang, dan konsultasi bisnis. Tim pelaksana melakukan sosialisasi PPK kepada mahasiswa sebelum dilaksanakan seleksi tenant. Kegiatan pembinaan yang telah dilakukan yaitu pelatihan kewirausahaan, pendampingnan penyusunan business plan, pengemasan produk, manajemen pemasaran, pengelolaan keuangan berbasis teknologi, magang, dan konsultasi bisnis. Hasil pelaksanaan PPK FKIP Universitas Cokroaminoto Palopo sudah terlaksana sesuai denganprogram dan target yang ingin dicapai. PPK FKIP merupakan program kewirausahaan berdimensi inovasi kreasi bisnis yang mengsinergikan dunia usaha dengan dunia pendidikan menggunakan teknik Warung Pendidikan disingkat Warpen. Selama dua tahun telah dihasilkan sepuluh wirausaha baru. Bidang usaha tenant tahun pertama yaitu Warpen Aksesoris, Warpen Dekorasi, Warpen Bimbingan Belajar, Warpen Analisis Data, dan Warpen Desain. Bidang usaha pada tahun kedua yaitu Warpen Tata Rias, Warpen Miniatur, Warpen Kuliner, Warpen Senam, dan Warpen Translater.Kata Kunci: Pengembangan, kewirausahaan, warpen,  mahasiswa, alumni.